Alternatif Perencanaan Oprit Jembatan Batanghari (STA 15+750) di Jalan Tol Ruas Jambi – Rengat - Lastiasih, Yudhi; Irfanil Azami, Fikri (Kadiri University, 2024)
Batanghari Bridge is part of the Jambi-Rengat Toll Road, faces significant challenges due its clay as the topsoil and dominant stratigraphy of sand. These contdition lead to high settlement potential and stability issues under heavy loads, requiring innovative to enhance stability and control costs. This study aims to evaluate the effectiveness of a combination of mortar foam and ordinary soil on at the Batanghari Bridge (STA 15+750). Observations were made at 2 abutments. Embankment material variation include 100% ordinary soil, 100% mortar foam, and combinations of 25%, 50%, and 75%. Results reveal that land subsidence from embankment loads and mortar foam remains high, necessitating alternative treatments. The findings indicate that for Abutment 1 benefits from Prefabricated Vertical Drain (PVD) and geotextile reinforcement, combined with 75% ordinary soil and 25% mortar foam. This approach reduces load and enhances stability at a cost of Rp29,045,321,602. Conversely, Abutment 2, with a 3-meter soft soil depth, achieves optimal results using 100% ordinary fill soil with replacement and geotextile reinforcement, costing Rp22,403,576,498. It was found that the differences in effective methods at Abutment 1 and Abutment 2 were caused by variations in subgrade conditions and soft soil depth at both locations. The study highlights the importance of tailoring embankment material and soil improvement methods to specific subgrade conditions. By demonstrating the effectiveness of combining material variations with soil improvement techniques, the findings contribute significantly to geotechnical engineering, offering practical, cost-efficient strategies for similar infrastructure projects